Sosialisasi Penggunaan Media Digital Yang Cerdas Bagi Pelajar di Desa Bandar Magodang - Mismahella, Igris; Wijaya, Aldy; Indah Riskiyah Harahap, Anggi; Dahlya Narpila, Suci (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
The aim of this activity is to provide data to students about the intelligent use of digital media which can influence the turn of events and the use of science in the eyes of the public. This business is named "Socialization of the Smart Use of Digital Media for Students in Bandar Magodang Village" Bintang Bayu District, Serdang Bedagai Regency. The main strategy used by students in this effort is an effort technique that provides material to help students understand how to make better use of advanced media. Through this local area administration, universities can support the use of intelligent and locally significant data innovation.